ANALISIS MUATAN HIGHER ORDER THINKING SKILLS (HOTS) DALAM SOAL ULANGAN HARIAN BAHASA INDONESIA KELAS VIII - Verawati Simorangkir, Agustina; Hasanah Harahap, Safinatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the Higher Order Thinking Skills (HOTS) content in the Indonesian language daily test items for grade VIII in three public junior high schools in Medan City based on Anderson and Krathwohl's revised Bloom's Taxonomy. A descriptive qualitative approach with content analysis method was used in this study. The primary data were 110 daily test items, supported by data from interviews with students. Data collection was carried out through documentation and interview techniques, while data analysis was carried out by classifying the test items into cognitive levels C4 (analyzing), C5 (evaluating), and C6 (creating). The results showed that 51 of the 110 analyzed test items (46.3%) were included in the HOTS category. This finding indicates that higher-order thinking skills have been accommodated in the preparation of assessment instruments, although the proportion is still lower than the low-level cognitive (LOTS) and medium-level cognitive (MOTS) questions. Thus, it can be concluded that the HOTS content in the Indonesian language daily test questions for grade VIII has been implemented in the three schools, but requires continuous reinforcement to be more optimal in developing students' critical thinking skills.